Controlling the Number of Branches and Surface Facets of Pd‐Core Ru‐Branched Nanoparticles to Make Highly Active Oxygen Evolution Reaction Electrocatalysts. Issue 67 (12th October 2020) - Myekhlai, Munkhshur; Benedetti, Tania M.; Gloag, Lucy; Poerwoprajitno, Agus R.; Cheong, Soshan; Schuhmann, Wolfgang; Gooding, J. Justin; Tilley, Richard D.
Abstract: Producing stable but active materials is one of the enduring challenges in electrocatalysis and other types of catalysis. Producing branched nanoparticles is one potential solution. Controlling the number of branches and branch size of faceted branched nanoparticles is one of the major synthetic challenges to achieve highly active and stable nanocatalysts. Herein, we use a cubic‐core hexagonal‐branch mechanism to synthesize branched Ru nanoparticles with control over the size and number of branches. This structural control is the key to achieving high exposure of active 10–11 facets and optimum number of Ru branches that enables improved catalytic activity for oxygen evolution reaction while maintaining high stability. Abstract : Branched ruthenium nanoparticles with control of branch size and number of branches are presented using a new approach. These controls enable improved catalytic activity for the oxygen evolution reaction (see figure).